National Sustainable School Program: the implementation in four regional schools in Joao Pessoa/PB - Silva, Maria Andresa; Santana, Luiz Carlos [UNESP] (Federal Univ Rio Grande, Inst Education, 2018)
The National Sustainable School Program (NSSP) is a political proposal developed to the basic education aimed at supporting the transition of the schools towards sustainability, connecting three axes: curriculum, management and physical space. This study shows an analysis about the implementation of NSSP in four regional schools in Joao Pessoa/PB, where we highlight the actions developed and the contributions from the program to the schools. This article is a result of a qualitative research of the type case study. The instruments used to collect the data were interviews with teachers and principals, political-pedagogical projects and action plans. Despite the obstacles found in NSSP's implementation, the schools have developed actions preferentially contemplating the physical space, and one of the most significant contributions was the exchange of knowledge between school and community.
Keywords: Environmental education; public policies; sustainable schools